1990
DOI: 10.1007/bf00228162
|View full text |Cite
|
Sign up to set email alerts
|

Parietal area 5 neuronal activity encodes movement kinematics, not movement dynamics

Abstract: A previous study reported that proximal-arm related area 5 neurons showed continuously-graded changes in activity during unloaded arm movements in different directions (Kalaska et al. 1983), which resembled the responses of primary motor cortex cells in several respects (Georgopoulos et al. 1982). We report here that loading the arm reveals an important difference between cell activity in the two areas. Loads were continuously applied to the arm in different directions. The loads produced large continuously-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
118
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(135 citation statements)
references
References 39 publications
13
118
0
2
Order By: Relevance
“…The elderly also exhibited additional activation in the left S2, left supramarginal gyrus, and right precuneus, consistent with previous results comparing the activation of old versus young subjects during various simple motor tasks (Hutchinson et al, 2002;Mattay et al, 2002;Ward and Frackowiak, 2003). These areas are known to be involved in the integration of somatosensory information to guide motor actions (Cavada and Goldman-Rakic, 1989;Kalaska et al, 1990;Ashe and Georgopoulos, 1994;Ferraina and Bianchi, 1994;Huttunen et al, 1996;Scott et al, 1997;Rizzolatti et al, 1998). Additionally, they seem to be related to the attentional effort required by a specific motor skill (Hari et al, 1990;Garcia-Larrea et al, 1991;Mima et al, 1998;Lam et al, 1999).…”
Section: Additional Brain Activation In the Elderly During Both Isolasupporting
confidence: 89%
“…The elderly also exhibited additional activation in the left S2, left supramarginal gyrus, and right precuneus, consistent with previous results comparing the activation of old versus young subjects during various simple motor tasks (Hutchinson et al, 2002;Mattay et al, 2002;Ward and Frackowiak, 2003). These areas are known to be involved in the integration of somatosensory information to guide motor actions (Cavada and Goldman-Rakic, 1989;Kalaska et al, 1990;Ashe and Georgopoulos, 1994;Ferraina and Bianchi, 1994;Huttunen et al, 1996;Scott et al, 1997;Rizzolatti et al, 1998). Additionally, they seem to be related to the attentional effort required by a specific motor skill (Hari et al, 1990;Garcia-Larrea et al, 1991;Mima et al, 1998;Lam et al, 1999).…”
Section: Additional Brain Activation In the Elderly During Both Isolasupporting
confidence: 89%
“…Neurons in areas PE and PF discharge at high rates when the animal projects his arm into the immediate extrapersonal space that surrounds him ("arm projection neurons") (25). In addition, it has been suggested that the kinematics (spatial parameters) of movement, but not its dynamics (forces required to produce movement), may be coded in the cortex of the superior parietal lobule (26). The present PET findings further demonstrate the involvement of these areas in imaginary spatiotemporal projections of the body as a whole in space, reflecting the internalized constraints of kinematic geometry (27).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most important original insight came from comparative studies of frontal motor areas and neurons in area 5 by Kalaska and co-workers (Crammond and Kalaska 1989;Kalaska and Crammond 1995;Kalaska et al 1983Kalaska et al , 1990 and Burbaud et al (1991), who demonstrated that neuronal activity in MI, PMd, and area 5 overlapped in time at the onset of reach and that area 5 neurons were directionally tuned during movements and postures. In addition, studies in deafferented monkeys by Seal et al (Seal and Commenges 1985;Seal et al 1982) indicated that area 5 neurons respond to reaching movements in the absence of somatosensory feedback.…”
Section: Neurons In Ppc Serve a Sensorimotor Rolementioning
confidence: 99%